How secondary inorganic aerosols from Delhi influence aerosol optical and radiative properties at a downwind sub-urban site over Indo-Gangetic Basin?. (1st March 2021) - Srivastava, Atul Kumar; Thomas, Abin; Hooda, Rakesh K.; Kanawade, Vijay P.; Hyvärinen, Antti -P.; Bisht, Deewan Singh; Tiwari, Suresh
Abstract: The particulate matters less than 10 μm sizes (PM10 ) were measured at a highly polluted urban environment of Delhi, and simultaneously at a downwind semi-urban site, Gual Pahari, in the north-west Indo-Gangetic Basin (IGB). The measurements were conducted during January–December 2008 to compare and contrast aerosol emissions, compositions and related optical and radiative properties for two different environments. While the total PM10 was about 30% lower at Gual Pahari as compared to Delhi, the total mass of water-soluble inorganic species (WSIs) was significantly enhanced ( 23%) at Gual Pahari. Amongst WSIs, the major secondary inorganic species (SIs) were about 52% higher at Gual Pahari as compared to Delhi, with elevated levels in the post-monsoon/winter seasons. In contrast, the major crustal species were about 76% higher at Delhi as compared to Gual Pahari, with elevated levels in the summer/monsoon seasons. This indicates a strong inter-seasonal spatial variability in aerosol sources and compositions at these sites. Further, the simulations using aerosol optical model had resulted mean absorption coefficient (babs ) and single scattering albedo (SSA) higher by about 50% and lower by about 18%, respectively, at Delhi (babs, 147 ± 63 M m −1 and SSA, 0.65 ± 0.12) as compared to Gual Pahari (babs, 73 ± 26 M m −1 and SSA, 0.79 ± 0.07). This reveals relative abundance of absorbing particles at Delhi compared to Gual Pahari. As a result, the estimated mean atmospheric forcing was 91 ± 23 W m −2 at Delhi, which was 55% higher as compared to Gual Pahari. This is further corroborated with observed higher heating rate at Delhi (2.5 ± 0.7 K day −1 ) as compared to Gual Pahari (1.1 ± 0.4 K day −1 ). Our results highlight that diverse near-surface emissions together with atmospheric processing leads to strong inter-seasonal spatial heterogeneity in aerosol chemical, optical and radiative properties between the adjacent distinct sites. This has an important implication for a city-scale air pollution modeling. Graphical abstract: Image 1 Highlights: Investigated the impact of secondary inorganic aerosols at two distinct adjacent sites in IGB. Water soluble inorganic species were abundant at Gual Pahari as compared to Delhi. The major crustal species were abundant at Delhi as compared to Gual Pahari. The two-fold increase in atmospheric warming at Delhi indicates dominant absorbing aerosols.